Studies on Schismatoglottideae (Araceae) of Borneo XVIII: Additional observations on Schottariella mirifica - Boyce, P.C; Wong Sin, Yeng (International Aroid Society, Inc., 2012)
Schottariella mirifica, the sole species of a Bornean endemic genus, is known from four localities on the Kanowit and Ai river catchments of western Sarawak, Malaysian Borneo. Based on recent fieldwork we here present expanded ecological information, and new morphological data, including descriptions and illustrations of the previously unknown mature infructescence.